Method for preparing high-toughness silk fibroin hydrogel as artificial tendon / ligament

By employing directional freezing and heating coaxial tension, the method effectively enhances the mechanical strength of silk fibroin hydrogel scaffolds, addressing the limitations of current tendon/ligament repair materials and achieving superior biocompatibility and degradability.

JP2025051585AActive Publication Date: 2025-04-04ZHEJIANG UNIV BINJIANG RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024064376
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-22
Filing Date
2024-04-12
Publication Date
2025-04-04
Estimated Expiration
2044-04-12

AI Technical Summary

Technical Problem

Current methods for preparing tendon/ligament repair materials, such as silk fibroin hydrogels, face challenges in achieving high initial mechanical strength and long-term maintenance, which is crucial for effective tendon/ligament repair.

Method used

A method involving directional freezing and heating coaxial tension of silk fibroin solutions is used to create high-strength silk fibroin hydrogel scaffolds. This process involves freezing the silk fibroin solution directionally, followed by sublimation and drying, and then heating and tensing the material above its glass transition temperature to enhance mechanical properties.

Benefits of technology

The resulting silk fibroin hydrogel scaffolds exhibit significantly improved mechanical strength, with maximum tensile stress increased by about 100 times, while maintaining excellent biocompatibility and degradability, facilitating effective tendon/ligament repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025051585000001_ABST
    Figure 2025051585000001_ABST
Patent Text Reader

Abstract

To provide a method for preparing a silk fibroin hydrogel scaffold having high strength, high biocompatibility, and biological microstructure.SOLUTION: There is provided a method for preparing a silk fibroin hydrogel scaffold having high strength, high biocompatibility, and biological microstructure for repair and reconstruction of tendons / ligaments by utilizing a natural silk fibroin material through directional freezing and coaxial hot stretching. The heating temperature must be higher than a glass transition temperature of the silk fibroin material, such that a maximum tensile strength of the silk fibroin hydrogel scaffold increases, a microscopic directional pore structure is formed, and finally a mechanically reinforced hydrogel scaffold with good biocompatibility is obtained.SELECTED DRAWING: Figure 12A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to Chinese Patent Application No. 2023112411598, filed on September 22, 2023, the entire contents of which, including but not limited to the specification, abstract, claims and accompanying drawings, are incorporated herein by reference.

[0002] The present invention relates to the technical field of hydrogel preparation, in particular to a method for preparing high-strength silk fibroin hydrogel, in particular to a method for preparing high-strength silk fibroin hydrogel that can be used as a rotator cuff, anterior / posterior cruciate ligament, medial retinacular replacement, etc. [Background technology]

[0003] Tendon / ligament injury is one of the common sports injuries. The tendons and ligaments of the human body are mainly composed of high-density type I collagen, with low cell content and weak angiogenic ability, so when damaged, they are difficult to heal naturally. Patients with large tendon / ligament injuries, such as giant rotator cuff tears and anterior cruciate ligament tears, often require supplementary treatment with patches. Currently, there are many methods for preparing tendon / ligament repair materials, but traditional techniques such as autologous materials and allogeneic materials have insufficient sources, making them prone to problems such as donor site complications, rejection, and disease transmission. Currently, a small number of artificial materials, such as the French "LARS" ligament and the Chinese "Ligetai", are used in clinical practice, but all of them have problems such as low tensile strength, poor biocompatibility, and difficulty in fusion with host tissue, which makes them prone to loosening of bone holes and fatigue fractures. These shortcomings lead to poor repair results for tendon / ligament injuries, and finding a scaffold material with both excellent mechanical properties and biocompatibility has become a research hotspot.

[0004] Silk fibroin is widely used in the manufacture of tissue engineering scaffolds, and has good biocompatibility, degradability, and excellent mechanical properties. Silk fibroin is abundant in source and can be extracted from raw silk. Raw silk has a unique protein polymer structure, which is composed of silk fibroin as the core and sericin attached to the surface. Silk fibroin is obtained by degumming treatment of raw silk. Silk fibroin contains 18 kinds of amino acids, most of which are glycine, alanine, and serine. Silk fibroin is completely degraded in the body, and during the decomposition process, the cellular microenvironment is rich in many amino acids, especially proline and lysine, which are the main raw materials for collagen synthesis. In silk fibroin, the repeat of GAGAG sequence can form a secondary structure beta sheet by self-organization, and this structure gives silk fibroin excellent mechanical strength and toughness. According to reports, the toughness of silk fibroin is better than the best synthetic materials. At the same time, silk fibroin has tunable mechanical properties. By adjusting the proportion of β-sheet structure in silk fibroin, the mechanical strength of silk fibroin material can be further improved, which is superior to the currently most commonly used degradable polymer materials such as collagen and polylactic acid. In addition, the surface of raw silk material is easy to process and modify, and it can be processed into various shapes from liquid state solutions to organic solid states such as gels, pipes, hydrogels, microspheres, and films. These properties of raw silk material make it promising for tissue engineering applications.

[0005] However, the mechanical strength of conventional silk fibroin is still difficult to achieve and maintain similar mechanical strength to that of human tendons / ligaments, so there is an urgent need to develop novel silk fibroin scaffolds with better initial mechanical properties and long-term maintenance. Summary of the Invention

[0006] In order to solve the above problems, the present invention provides a method for preparing a high-strength silk fibroin hydrogel scaffold for tendons / ligaments, using natural silk fibroin material, and by using the processing method of directional freezing and heating coaxial tension (higher than the glass transition temperature of silk fibroin), the silk fibroin hydrogel scaffold can achieve an improvement in the maximum tensile strength, and has a fine directional pore structure, resulting in a mechanically reinforced hydrogel scaffold with good biocompatibility, which can be used to manufacture tendon / ligament scaffolds, which can achieve mechanical strength similar to that of the tendons / ligaments of the human body (e.g., rotator cuff, cruciate ligament, Achilles tendon), and also have excellent biocompatibility and degradability. The micromorphology of the scaffold has micron-scale directional pores, which are conducive to directional cell growth on the surface and inside of the material, and can achieve higher repair efficiency.

[0007] Thus, according to one aspect of the present invention there is provided a method for preparing a hydrogel, the method comprising the steps of:

[0008] (1) performing directional freezing on a silk fibroin solution to change a solvent in the solution from a liquid state to a solid state;

[0009] Step (2) of sublimating and drying the solid-state solvent in the product obtained in step (1);

[0010] and (3) heat-stretching the freeze-dried product to obtain the hydrogel.

[0011] In some embodiments, the sublimation method in step 2 can be various, but any method that can directly change the solvent from a solid state to a gaseous state can be used, and in this method, the sublimation method can be selected according to the nature of the solvent, for example, freeze-drying is commonly used. If the solvent is water, the solidified ice block can be directly put into a freeze dryer for freeze-drying, whereby the water is evaporated or sublimated directly from the solid-state ice, leaving the final silk fibroin. In some embodiments, the solvent is completely evaporated, where the sublimation can be 100% evaporated, or 99%-80% of the solvent can be directly sublimated from the solid state to the gaseous state.

[0012] In some embodiments, the solvent of the silk fibroin solution includes water, such as deionized water, pure water, mineral water, any water molecule in nature, etc. Of course, the solvent is not limited to water, but any other solvent that can dissolve silk fibroin can be used as long as it changes to a solid state at low temperature.

[0013] In some embodiments, the silk fibroin solution of the present invention is obtained by degumming natural raw silk. It should be understood that in some embodiments, silk fibroin obtained by degumming raw silk can be directly purchased. In some embodiments, artificially synthesized silk fibroin can also be used.

[0014] The "directional freezing" defined in the present invention means that a polymer solution is placed in a temperature field and cooled, and as the temperature decreases, the solvent (usually water) freezes in a gradient in the direction of the gradually decreasing temperature, and the ice crystal pillars generated by the gradual freezing push out the polymer chains to rearrange directionally and embed them between the ice crystal pillars. In general, a cylindrical or rectangular container (cavity) is placed on or in contact with a cold source, and the cavity is filled with a silk fibroin solution, which gradually freezes in the direction away from the contact point with the cold source, and ice crystal pillars are also gradually formed along this direction. That is, during freezing, the solvent in the solution gradually freezes and solidifies, gradually changing from a liquid state to a solid state, and ice crystal pillars (when the solvent is water) are formed along the direction of the gradual freezing. In this process, the ice crystals as an orientation template for the polymer chains function as a physical confinement and play a role in directionality. The term "gradually" as used in this invention is a relative concept. When a certain volume of solution comes into contact with a cold source, the solution always first starts to change from a liquid state to a solid state near the cold source, and then as time passes, the solution solidifies, and continues to move from a direction approaching the cold source to a direction away from the cold source until the entire solution becomes solid. During this process, an ice crystal structure is gradually formed, and as time passes, the ice crystal structure gradually stretches, and the stretching direction becomes substantially the same as the solidification direction.

[0015] The "directional freezing" described in this specification can also be understood as follows. When a solution is brought close to a temperature at which the solvent solidifies (when there is one freezing temperature source), the solvent in the solution gradually solidifies from the direction close to the freezing temperature source to the direction away from the freezing temperature source, realizing gradual solidification from a liquid state to a solid state. Such solidification is directional, and when the freezing temperature is a single temperature source, the solidification direction is one direction, and when the solution is between two freezing temperature sources, the solvent in the solution gradually solidifies from both ends toward the center, and the solidification direction is two directions. Indeed, when the freezing temperature source is in the center of the solvent, the solvent gradually solidifies from the center toward the outside, and the solidification direction is a direction of dispersion from the center of the solvent to both ends. Whether it is a single direction, two opposing directions, or a diverging direction, they are all specific implementation methods of directional freezing and solidification. In some embodiments, the above-mentioned directional freezing is to change the solvent that dissolves silk fibroin from a liquid state to a solid state, for example, to change water from a liquid state to a solid state, for example, to exist in the state of ice.

[0016] Of course, directional freezing does not include such methods, except for the method of placing all of the silk fibroin-containing solutions under a refrigerator and placing them in a three-dimensional surrounding freezing environment where the ambient temperature is lower than the freezing temperature of the solution solvent, which can also change the solvent from a liquid state to a solid state, but is not within the meaning of "directional freezing" as described in this invention.

[0017] Therefore, directional freezing can form heterogeneous structures in various directions, and materials can be arranged in various directions in space, and the mechanical properties of the oriented direction using directional freezing are much stronger than those without directional freezing. Furthermore, the space occupancy effect of ice crystals or solvent solid phase increases the local aggregation degree of silk fibroin molecules, further improving the mechanical properties. Compared with non-directionally frozen silk fibroin hydrogels, the maximum tensile stress of directional frozen silk fibroin hydrogels can be increased several times. Furthermore, the directional freezing technique allows the silk fibroin solution to form a parallel arranged pipe structure with parallel pores of 5-10 μm, which resembles the tendon microstructure. This microstructure can, on the one hand, guide and stimulate tendon stem cells to differentiate into tendon cells, and on the other hand, promote the penetration, growth and directional arrangement of cells into the inside of the scaffold, thereby promoting the efficiency and effectiveness of tendon regeneration.

[0018] In some embodiments, in order to facilitate specific directional freezing, the solution containing silk fibroin can be placed in a container, and then directional freezing can be performed on the solution in the container. For example, the container can be a container of any shape, and the shape of the container can be any shape, such as a sphere, a cube, a rectangular parallelepiped, or other container shapes. In some embodiments, the internal space of the container is a rectangular parallelepiped, and for example, the cross section of the rectangular parallelepiped can be any shape, such as a circle, a rhombus, a square, an ellipse, and the like, and for example, the container is a rectangular parallelepiped, and thus, when a solution is poured or placed into such a container, the solution is cooled from one end by the freezing source, and gradually freezes and solidifies from one end to the other end, and gradually freezes along the vertical direction of the container, and the solvent changes from a liquid state to a solid state along the vertical direction, resulting in ice formation.

[0019] In some embodiments, step (3) involves directional stretching of the material. In some embodiments, the direction of the directional stretching is the same as the direction of directional freezing. For example, if the silk fibroin solution freezes and solidifies in a single direction, the stretching direction is also a single stretching direction, and is substantially the same as the freezing direction. It should be understood that the directional freezing is from one end to the other in a single direction (single arrow direction), but the stretching can be from two points outward (double arrow direction), but the stretching directions are not the same, but are all collinear. For example, the directional freezing is from one end to the other along the vertical direction in a rectangular container, and the stretching can be along the vertical axis, or in two directions, or along the vertical axis.

[0020] In some embodiments, the silk fibroin material is heated to a certain temperature during tensioning. In some embodiments, the heating temperature is higher than the glass transition temperature of the silk fibroin material, and the mechanical properties of the material can be significantly improved by heating coaxially or directional tensioning. Coaxial tensioning with directional freezing or tensioning under a direction with directional freezing direction can both impart a certain strain to the material and stretch the material to a certain length, and the molecules in the material are rearranged under the action of the generated tensile stress, so that the material has a specific oriented structure in the tensioning direction, further improving the tensile strength in that orientation.

[0021] In addition, amorphous polymers have three mechanical states: glass state, high elasticity state, and viscous flow state. When the temperature is low, the material is in a hard solid state similar to glass, and the glass state is a state in which only very small deformation occurs even when an external force is applied. When the temperature continues to rise to a certain range, the deformation amount of the material increases significantly, and the state in which the deformation amount is relatively stable in a certain temperature range thereafter is a state in which the high elasticity state. The glass transition temperature (Tg) refers to the temperature corresponding to the transition from the glass state to the high elasticity state. Silk fibroin is in a glass state at normal or room temperature (25 degrees Celsius), and can only undergo slight deformation even under coaxial tension. When heated, silk fibroin rises above Tg and enters a high elasticity state, and the movement of silk fibroin molecules becomes active and the range of movement expands. Under this state, the silk fibroin material is easy to deform and can be stretched to a higher magnification during coaxial or directional tension, and the intensification of molecular motion helps to form an orientation at the molecular level.

[0022] As for the tensile equipment, the tensile can be completed automatically using conventional equipment, such as using a high-temperature mechanical tester to complete the tensile. The high-temperature mechanical tester is a scientific instrument used in the field of materials science, and mainly includes an extensometer, a high-temperature furnace for heating, and a bar and plate clamp for fixing the tensile material such as the silk fibroin of the present invention, the directional frozen silk fibroin material, etc. For example, all the equipment introduced on this website can complete the tensile of the present invention. http: / / www.cxwannengsyj.com / html / 2019 / gaodiwen_0521 / 1596.html?sdclkid=ALos152NxSDibL-pA52G&bd_vid=10212208613159825381. , https: / / www.zhongguoqingji.com / 685cc91a-bdab-2768-53cf-5bde625d2d7f / GDWWNSYJ.shtml?bd_vid=12561170255290571953,

[0023] The glass transition temperature of dried silk fibroin film is about 178°C, and when water molecules are used as a plasticizer, the conditions used in the present invention can reduce the glass transition temperature to 77°C, thereby greatly reducing the difficulty of operation and reducing costs.

[0024] Therefore, in some embodiments, the present invention freeze-dries the directional frozen silk fibroin, evaporates the solidified solvent to leave only the silk fibroin itself, and then crosslinks and / or hydrates it, and then performs directional tension, which can be performed at a low temperature, reducing the difficulty of operation and reducing costs. The present invention can increase the maximum tensile stress of silk fibroin hydrogel by about 10 times by performing coaxial tension on hydrated silk fibroin at different temperatures above Tg and different tensile strains. The directional freezing and heating tension used in the present invention also has a significant synergistic effect, whereby the maximum tensile strength of silk fibroin hydrogel is increased by almost 100 times, and the biocompatibility is also excellent, and the fine directional pore structure is conducive to cell growth and further to tendon injury repair.

[0025] Heat tension needs to be performed after directional freezing, and coaxial tension needs to be performed along the direction of directional freezing. 1. The directional freezing step is a prerequisite for heat tension. If tension is performed directly without directional freezing, the silk fibroin hydrogel will be directly broken; 2. If coaxial tension is not performed in the directional freezing direction after directional freezing, the silk fibroin hydrogel will also be directly broken.

[0026] Furthermore, the above preparation method comprises:

[0027] (1) injecting a silk fibroin solution into a mold and performing directional freezing to obtain a silk fibroin ice block;

[0028] (2) freeze-drying the silk fibroin ice block to crosslink it, and then immersing it in water to hydrate it to obtain a hydrogel;

[0029] and (3) subjecting the hydrogel to heat tension.

[0030] In some embodiments, the direction of the heat stretch coincides with the direction of the directional freezing.

[0031] Furthermore, the directional freezing described in step (1) refers to the directionally generating ice crystals when the silk fibroin solution in the mold approaches the contact surface of the freezing source and moves away from the contact surface of the freezing source when the freezing source is brought closer to the mold. In some embodiments, the temperature of the freezing source is less than -20°C, -10°C, -5°C, -2°C, or -1°C.

[0032] Any device or product that has the effect of lowering the temperature can be used as the freezing source of the present invention, or in any case, a freezing source that can solidify the solvent in the solution containing silk fibroin is acceptable. For example, a freezing source with a different temperature can be set according to the freezing point temperature of the solvent. The "freezing source" set in the present invention depends on the solvent that dissolves silk fibroin, and also changes depending on the environmental conditions. If the solvent and environment are different, the freezing and solidifying temperature of the solvent will also be different. For example, if the solvent is pure water, the freezing point of water will decrease as the atmospheric pressure increases, and the freezing temperature of water will be below 0°C. Naturally, the lower the temperature, the shorter the freezing time of water. In addition, the solution has a certain height (for example, the height of the solution is 1 mm to 200 cm), and the time until the entire solution is completely solidified will also be different. For example, if the solvent is water and the thickness is 1 mm, solidification can be achieved at 0°C or below, and if the thickness is 10 cm or 20 cm, a lower temperature and a longer time may be required. It should be understood that a person skilled in the art can arbitrarily select according to the actual situation after reading the contents of the present invention, and ultimately, there is no problem as long as the solution containing silk fibroin can be solidified.

[0033] In some embodiments, the freezing source can be realized by using liquid nitrogen. In some embodiments, when performing directional freezing, one end of the metal element is connected to liquid nitrogen, and the other end is connected to one end of a container containing the silk fibroin solution, thereby achieving directional freezing of the silk fibroin solution. In some embodiments, step (1) is to put the silk fibroin solution into the cylindrical space of the mold, place the mold above the metal rod, and immerse one side of the metal rod in liquid nitrogen.

[0034] In some embodiments, the metal rod as the freezing source is located below the mold and is in full contact with the bottom surface of the mold, and during freezing, the ice crystals of the silk fibroin material grow upward from the cold source below, with a certain directionality, which is perpendicular to the bottom surface in contact with the freezing source, and then grow in the direction away from the freezing source.

[0035] In some embodiments, the metal rod as the freezing source is located on the side of the mold and is in full contact with the side of the mold, and upon freezing, the ice crystals of the silk fibroin material start to grow directionally from the side that is in contact with the freezing source, and the growth direction of the ice crystals is perpendicular to the bottom surface of the freezing source, and then grow in the direction away from the freezing source.

[0036] In some embodiments, the metal rod as the freezing source is located on the top surface of the mold and is in full contact with the top surface of the mold, and during freezing, the ice crystals of the silk fibroin material start to grow downward from the top surface that is in contact with the freezing source, and the growth direction of the ice crystals is perpendicular to the bottom surface of the freezing source, and then grow away from the freezing source.

[0037] In some embodiments, step (1) is to pour the silk fibroin solution into a mold with a cylindrical space of 4*4*20 mm. The mold is placed on an aluminum rod with a width that completely covers the contact surface with the mold, and one side of the aluminum rod is immersed in liquid nitrogen. After 10 minutes, the mold is removed, the silk fibroin ice block in it is taken out, and placed in a refrigerator at -80°C overnight.

[0038] Furthermore, after directional freezing and drying, the silk fibroin is cross-linked. Thus, in some embodiments, for example, the cross-linking described in step (2) is chemical cross-linking or enzymatic cross-linking.

[0039] Since silk fibroin is water soluble, it also needs to be crosslinked to form a hydrogel; on the one hand, crosslinking can make the silk fibroin scaffold stable in aqueous solution, and on the other hand, it can further improve the strength of the material.

[0040] It should be noted that the crosslinking process is performed after the completion of directional freezing, because if the molecular structure is fixed by crosslinking first, the ice crystals will not be able to align directionally as they grow during directional freezing, and fine directional pores will not be able to form, so the scaffold will eventually lose its directional structure.

[0041] The present invention can use any crosslinking method, such as ethanol crosslinking, other chemical crosslinking, enzyme crosslinking, etc., as long as the silk fibroin material can be crosslinked, it can be used in the present invention and is within the protection scope of the present invention.

[0042] Furthermore, step (2) is to freeze-dry the silk fibroin ice block in a freeze dryer, immerse it in absolute ethanol for cross-linking, and then immerse it in water for complete hydration.

[0043] In some embodiments, the present invention uses absolute ethanol for crosslinking, but the silk fibroin ice block needs to be freeze-dried before crosslinking, and when the solvent is water, the ice block is evaporated and removed while retaining the directional silk fibroin. This is because if the silk fibroin ice is directly crosslinked without freeze-drying and the low-temperature silk fibroin ice block is contacted with relatively high-temperature ethanol, the ice crystals will melt before ethanol crosslinking and the internal microstructure will be broken. After the silk fibroin ice block is freeze-dried, a complete silk fibroin scaffold with a fine directional structure is obtained, which is then put into absolute ethanol for intermolecular crosslinking to form a more stable silk fibroin hydrogel structure.

[0044] In some embodiments, after crosslinking, it can also be immersed in water to hydrate, the reasons for which are as follows: The glass transition temperature of the dried silk fibroin material is about 178°C, and with the change in humidity, if water molecules are used as a plasticizer, the glass transition temperature can be reduced to below 77°C, and after the glass transition temperature is reduced, the difficulty of heating and tensioning is greatly reduced and the cost is reduced; and when coaxial tensioning is performed at a temperature above 100°C, the water in the hydrogel will evaporate quickly, resulting in the loss of water molecules as a plasticizer, making the hydrogel brittle and limiting the tension length. Therefore, hydrated silk fibroin can be achieved at 100°C or below, such as 95°C, 85°C, 75°C, 65°C, 55°C, 45°C, 35°C, 25°C or below 15°C, preferably at a temperature below 77°C. Sufficient hydration refers to immersing in water to the extent that the quality of the scaffold is basically unchanged, which indicates that the hydration is sufficient, and generally immersed for more than 48 hours.

[0045] In some embodiments, the silk fibroin ice blocks can be placed in a freeze dryer and freeze-dried for 72 hours to obtain a dry scaffold, which is then immersed in absolute ethanol for 6 hours for crosslinking, and then immersed in water for 48 hours for complete hydration.

[0046] Furthermore, the hot tension described in step (3) refers to heating to above the glass transition temperature of silk fibroin and then performing coaxial tension, and the direction of the coaxial tension is consistent with the direction of directional freezing.

[0047] When the direction of coaxial tension coincides with the direction of directional freezing, the resulting scaffold has better mechanical properties and fine directional pores, conducive to cell growth.

[0048] After directional freezing, drying and crosslinking, the hydrogel appears as vertical stripes, and the direction of the fine pores formed by directional freezing is visible to the naked eye. In this case, the silk fibroin is heated above its glass transition temperature and subjected to directional coaxial tension in the same direction, achieving a rapid increase in mechanical strength.

[0049] Furthermore, step (3) is to first preheat the hydrated hydrogel at a temperature of 25-130° C., and then stretch the material to 30-90% of its initial length.

[0050] In some embodiments, the heating temperature may be equal to or greater than the glass transition temperature of silk fibroin, and may reduce the glass transition temperature of the hydrated silk fibroin hydrogel below 77°C, for example to 25°C.

[0051] Furthermore, step (3) is to first preheat the hydrated hydrogel at a temperature of 25-130°C, then stretch the material to 30-90% of its initial length, hold for 15 minutes, and then take it out and immerse it in water to hydrate, thereby obtaining the final hydrogel.

[0052] In some embodiments, the hot tensioning can be completed in a hot tensioning device, such as a high temperature mechanical tester, provided that the heating and tensioning can be performed simultaneously.

[0053] In some embodiments, the pre-tension force for the heat tensioning need only be capable of tensioning the hydrogel such that the hydrogel does not significantly shrink due to the pre-tension force.

[0054] In some embodiments, the heating tension ratio is not constant, and as long as tension is applied, the mechanical properties of the hydrogel can be improved, so that tension can be applied according to actual needs, and the scaffold only needs to be prevented from breaking. If tensioned to more than 90% of the initial length, the material may be partially broken.

[0055] In some embodiments, step (3) is to apply a pre-tensile force of 2 N to the hydrated hydrogel, pre-heat at 95°C for 5 minutes, and then tensile the material to 30-90% of its initial length at a rate of 10 mm / min at 95°C, hold for 15 minutes, and then remove and immerse in water to hydrate to obtain the final hydrogel.

[0056] Furthermore, the method for preparing the silk fibroin solution described in step (1) is as follows: After removing the silkworm pupae from the raw silk, they are placed in a 0.02M sodium carbonate solution and boiled for 30 minutes to remove the rubber, and the silk fibroin fibers after the rubber removal are dried in a fume hood for 12 hours, and then dissolved in 9.3M lithium bromide at 60°C for 4 hours, and the solution is dialyzed for 72 hours using a dialysis bag to remove the lithium bromide, and the resulting solution is naturally dried in a fume hood for 6 hours to obtain a silk fibroin solution with a concentration of 15%.

[0057] The present invention uses natural raw silk, and after removing rubber from the raw silk, prepares a silk fibroin solution, performs directional freezing on the silk fibroin solution, freeze-dries it, and then crosslinks it using absolute ethanol. The obtained scaffold is then fully hydrated, and then stretched at a speed of 10 mm / min to 60% of its initial length under high temperature conditions above the glass transition temperature (95°C), and held for 15 minutes. The scaffold is then removed and hydrated to obtain the final hydrogel.

[0058] In another aspect, the present invention provides a use of a method for improving the mechanical properties of a material, the method comprising first subjecting the material to directional freezing, freeze-drying, and then subjecting it to coaxial heating and drawing, the heating temperature being equal to or higher than the glass transition temperature of the material, the material being PVA, gelatin, etc.

[0059] The present invention provides a method for the combined processing of heating tension and directional freezing, where directional freezing not only provides the material with a fine directional pore structure, but also improves the mechanical properties of the material through the formation of the anisotropic structure. Furthermore, if the material after directional freezing is further subjected to heating tension above the glass transition temperature, the mechanical properties of the material can be further significantly improved and the maximum tensile stress of the material can be improved. At the same time, the micron-scale directional pore structure of the hydrogel, on the one hand, guides and stimulates cell differentiation through the microtopological topography, and on the other hand, is conducive to the infiltration of cells on the scaffold, promoting tissue repair.

[0060] The combined processing method of directional freezing and heat tension provided by the present invention is suitable for improving the mechanical properties of not only silk fibroin materials but also other materials.

[0061] In yet another aspect, the present invention provides a use of silk fibroin hydrogel for manufacturing a rotator cuff patch or anterior cruciate ligament replacement, the silk fibroin hydrogel being obtained by directional freezing, freeze-drying and then heating and stretching a silk fibroin solution, the heating temperature being equal to or higher than the glass transition temperature of silk fibroin.

[0062] In summary, the present invention pre-protects the processing method of tension above the glass transition temperature (called hot tension) and the collaborative processing method of hot tension and directional freezing, which can be used to improve the mechanical properties of the material and obtain surface micro-topography, which is helpful in improving the efficiency of tendon repair.

[0063] The silk fibroin hydrogel scaffold provided by the present invention has the following beneficial effects:

[0064] 1. Excellent mechanical properties. The maximum stress of conventional silk fibroin hydrogels is about 0.02-0.2 MPa, but the present invention can reach 10 MPa or more, which is an increase of several hundred times.

[0065] 2. The directional topology of the hydrogel surface promotes the directional alignment of tendon stem cells.

[0066] 3. Excellent biocompatibility: The raw silk material itself has excellent biocompatibility, and the preparation process of the hydrogel scaffold does not use organic reagents that are difficult to remove, so the final scaffold has high biocompatibility.

[0067] 4. Raw silk materials are easier to obtain than autologous tendons, and the preparation process is simple.

[0068] 5. The proposed directional freezing and heat-tensile collaborative processing method is suitable for improving the mechanical properties of not only silk fibroin materials but also other materials. [Brief description of the drawings]

[0069] [Figure 1A] FIG. 1A is a flow chart of the preparation of silk fibroin hydrogel scaffolds, where FIG. 1A is a schematic diagram illustrating the principle of directional freezing, the cone-in-cube structure is a schematic diagram of the ice crystal structure, the black dots are water molecules, and the curved lines between the water molecules are a schematic diagram of silk fibroin. [Figure 1B] FIG. 1B is a schematic diagram illustrating the principle of cross-linking and hydration. [Figure 1C] FIG. 1C is a schematic diagram illustrating the principle of directional pulling. [Figure 2A] FIG. 1 is a schematic diagram of a specific embodiment (Example 1) of the present invention in which a mold containing silk fibroin solution is placed on an aluminum rod for directional freezing, and one end of the aluminum rod is immersed in liquid nitrogen. [Figure 2B] FIG. 2 is a schematic diagram of the principle operating structure of directional freezing in a specific embodiment of the present invention. [Diagram 3] 1 shows SEM images of hydrogel scaffolds that were heat-stretched without, during, and after directional freezing in Example 2. As can be seen, the hydrogel without directionally freezing exhibits an irregular pore structure at the microscopic level, while the hydrogel that was directionally frozen exhibits a directional pore structure at the microscopic level. [Figure 4A] FIG. 10 is a comparison diagram of tensile curves without directional freezing and during directional freezing in Example 2. [Figure 4B] FIG. 13 is a diagram showing the mechanical comparison results between without directional freezing and during directional freezing in Example 2. [Diagram 5] 1 shows a stress-strain curve obtained by carrying out a tensile test on an ND15-based hydrogel using a mechanical universal testing machine in Example 3. [Figure 6] 1 shows a stress-strain curve obtained by performing a fracture toughness test on an ND15-based hydrogel using a mechanical universal testing machine in Example 3. [Figure 7] Photographs of the notched ND15 hydrogel during the pulling process in Example 3 (leftmost photograph is the start of pulling, center is the break during the pulling process, and rightmost photograph is the complete break during the pulling process). [Figure 8A] FIG. 13 is a comparison diagram of the tensile curves of silk fibroin hydrogels with different concentrations in Example 4. [Figure 8B] FIG. 13 shows the mechanical comparison results of silk fibroin hydrogels with different concentrations in Example 4. [Figure 9] FIG. 1 shows the DSC diagram of the silk fibroin hydrogel prepared in step c in Example 5. [Figure 10A] FIG. 13 is a comparison diagram of the tensile curves of silk fibroin hydrogels obtained by changing the heating temperature in step d of Example 5. [Figure 10B] FIG. 13 shows the mechanical comparison results of silk fibroin hydrogels obtained by changing the heating temperature in step d of Example 5. [Figure 11A] FIG. 13 is a comparison diagram of the tensile curves of silk fibroin hydrogels obtained by changing the tensile magnification in step d in Example 6. [Figure 11B] FIG. 13 shows the mechanical comparison results of silk fibroin hydrogels obtained by changing the tensile magnification in step d in Example 6. [Figure 12A]12A shows the tensile stress-strain curves of the three groups of hydrogels in Example 7, and the calculated maximum tensile stress and Young's modulus (FIG. 12B). [Figure 12B] 12A shows the tensile stress-strain curves of the three groups of hydrogels in Example 7, and the calculated maximum tensile stress and Young's modulus (FIG. 12B). [Figure 13] 13 is a HE staining image of silk fibroin hydrogel used as a splint to repair rabbit Achilles tendon after rupture in Example 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0070] The preferred embodiments of the present invention will now be described in more detail with reference to the drawings. It should be noted that the examples described below are intended to facilitate the understanding of the present invention without limiting the present invention. The raw materials and equipment used in the specific embodiments of the present invention are all known products and can be obtained by purchasing them commercially.

[0071] Example 1 Preparation of silk fibroin hydrogel scaffolds provided by the present invention The preparation method of silk fibroin hydrogel scaffold provided by this example is carried out according to the flow shown in FIG. 1, and the method includes the following steps:

[0072] a. The silk fibroin solution was prepared by boiling silkworm pupae (5 g) in 0.02 M sodium carbonate solution (2 L) for 30 minutes, drying the silk fibroin fibers after removing the rubber substance in a fume hood for 12 hours, dissolving them in 9.3 M lithium bromide at 60°C for 4 hours, dialyzing the solution for 72 hours using a dialysis bag to remove the lithium bromide, and naturally drying the resulting solution in a fume hood for 6 hours to obtain a 15% silk fibroin aqueous solution.

[0073] b. In directional freezing, silk fibroin solution is put into the cylindrical space of the handmade mold, and there is a 4*4*20mm cylindrical space (cubic opening, size 4*4mm, depth 20mm) in the mold, the space contains silk fibroin aqueous solution, and the space is usually filled with solution, where the material of the mold can be any metal such as aluminum, iron, alloy, etc. The grinding material in this embodiment is an aluminum alloy material. Of course, in other examples, any space such as a cylinder, a cube, a rectangular parallelepiped, etc. is allowed, and all of these spaces have openings to realize freezing, and the silk fibroin solution can enter the space to realize directional freezing.

[0074] One end of the aluminum rod is immersed in liquid nitrogen (FIG. 2A), thus the aluminum rod is cooled by liquid nitrogen and the temperature drops, and the mold containing silk fibroin solution is placed on the other end (the bottom of the cylindrical space is in contact with the liquid), and the 4*4mm bottom of the mold is completely in contact with the surface of the aluminum rod, and due to the temperature transfer effect of the aluminum rod, directional freezing is carried out gradually from the bottom of the cylindrical space upwards, and the solution gradually becomes solid from the bottom, especially the water gradually becomes solid from the bottom upwards, and the formed ice crystals also gradually spread from the bottom to the opening (the direction of the arrow in step 1 in FIG. 1A). After 10 minutes, the mold is removed, and the silk fibroin ice block in it is taken out and placed in a refrigerator at -80°C overnight.

[0075] For example, referring to FIG. 2B, the opening 10 of the cylindrical space 12 is at the top, in this case one end 13 of the aluminum rod may be located at the bottom 11, or the bottom 11 of the cylindrical space may be located on the surface of the aluminum rod, and the other end 14 of the aluminum rod contacts liquid nitrogen, thus the solution in the cylindrical space gradually solidifies from the bottom 11 toward the opening 10, and as a result, the formed ice crystals also spread from the bottom toward the opening, and directional freezing is performed in the direction of the arrow in FIG. 2(b).

[0076] c. For ethanol cross-linking, the silk fibroin ice block was placed in a freeze dryer and freeze-dried for 72 hours, and the ice block was evaporated to obtain a dry scaffold. The silk fibroin scaffold was then immersed in absolute ethanol for 6 hours for cross-linking, and then immersed in water for 24 hours for complete hydration.

[0077] d. In the heated coaxial tension test, a high temperature mechanical tester (TSE type, WANCE, model number: ETM105D) is used to clamp the hydrogel hydrated in step C above, apply a pre-tension force of 2N to the hydrated hydrogel, preheat at 95°C for 5 minutes, then at a temperature of 95°C, the material is stretched to 60% of its initial length at a speed of 10 mm / min, held for 15 minutes, and the temperature is raised from the surroundings toward the clamp (heat source), and then it is taken out and immersed in water for 24 hours to hydrate, to obtain the final hydrogel. The tension direction is the same as that of the cylindrical space for freezing (the direction of the arrow in Figure 1C is the vertical tension to both ends), i.e., the tension direction is along the vertical upward direction to a depth of 20 mm, which can be understood as vertical tension.

[0078] Example 2. Effect of directional freezing on silk fibroin hydrogels In this example, two groups of silk fibroin solutions were taken respectively, one group was subjected to directional freezing according to the method provided in Example 1, and then directional silk fibroin hydrogel scaffolds (DF) were prepared by ethanol crosslinking; for the second group, directional freezing was not performed, and the solution prepared in step a was placed in a mold, directly placed in a refrigerator at -80 °C, freeze-dried, and then crosslinked and hydrated with ethanol to form non-directional silk fibroin hydrogels (ND). SEM images of the prepared hydrogel scaffolds of the two groups are shown in Figure 3, and Figure 3b (middle) is a parallel aligned pipe structure formed after directional freezing, with 1-10 μm parallel pores similar to the surface topological structure of tendons. Figure 3a is an SEM image of a non-directional hydrogel scaffold (far left), which is significantly different from the directionally aligned pipe structure in Figure 3b. The tensile curves of the two groups of silk fibroin hydrogels are shown in Figures 4A-4B, where Figure 4A is a graph showing the relationship between the tensile ratio and the tensile stress, and Figure 4B is a graph showing the comparison between Young's modulus and the tensile stress. Here, DF 15 refers to DF prepared with silk fibroin at a concentration of 15%, and ND 15 refers to the NDs prepared with silk fibroin at a concentration of 15%. As is evident from Figure 4, the tensile stress and Young's modulus of silk fibroin prepared by directional freezing are significantly improved, where the tensile stress increases by about 6 times and the Young's modulus increases by about 1 times.

[0079] Example 3 Directional freezing step as a prerequisite for heat stretching This example only concerns silk fibroin hydrogel, and its preparation process is as follows: the solution prepared in step a is put into a mold and directly placed in a refrigerator at -80°C (non-directional), then freeze-dried and cross-linked with ethanol to obtain non-directional silk fibroin hydrogel (ND 15 ) is formed. ND 15 The mechanical properties of the hydrogels in the group were tested, and through tensile testing, the stress-strain curves shown in Figure 5 were obtained. As shown in Figure 5, 15The mechanical properties of ND hydrogel are poor, with a maximum stress of only 0.21 MPa and a breaking strain of about 32%, which is low in strength and toughness. In order to further test the fracture toughness of the material, pure shear test experiments are carried out on the ND hydrogel. In the tests, a pair of ND hydrogels is tested each time, which includes the original complete hydrogel (Initial ND) and the hydrogel with a notch created (Notched ND), and a tensile test is carried out on each pair of hydrogels to obtain the stress-strain curve shown in Figure 6, and the fracture toughness is obtained by calculation. Figure 7 shows the stress-strain curve of the notched ND during the tensile process. 15 As shown in Figure 7, a photograph of the hydrogel is shown. 15 The notch in ND widens rapidly during the tensile process, causing rapid fracture of the hydrogel at small strains (less than 20%). Combined with the calculated fracture toughness shown in Figure 6, ND 15 Hydrogels exhibit poor fracture toughness. 15 Hydrogels have low mechanical strength and low toughness, leading to fracture at small strains and making them unsuitable for subsequent hot tensile testing. In other words, the directional freezing step is a prerequisite for hot stretching.

[0080] In addition, DF prepared by directional freezing 15 In the case of DF, if the directional freezing is not performed according to the direction of directional freezing, excellent mechanical properties cannot be obtained, and the material is difficult to tensile and prone to fracture. 15 In the case of DF, the pipes are easily separated from each other due to the directional arrangement of the pipe structure, and the heating tension is not performed according to the direction of directional freezing during tensioning. 15 becomes prone to breakage and cannot successfully complete the combined preparation process of heat pulling and directional freezing.

[0081] Example 4 Effect of silk fibroin concentration on silk fibroin hydrogels In this example, four groups of silk fibroin solutions are taken, and their concentrations are 5%, 10%, 15%, and 20%, respectively. Each group is subjected to directional freezing according to the method provided by Example 1, and then 60% directional tension is applied coaxially at 95 ° C to prepare silk fibroin hydrogel scaffolds. The tensile properties of the prepared two groups of hydrogel scaffolds are investigated, and the tensile properties are tested using a biomechanical testing machine. The tensile curves of the detected silk fibroin hydrogels with different concentrations are shown in Figure 8, where the figure on the left is the relationship between the tensile magnification and the tensile stress, and the figure on the right is the comparison between Young's modulus and the tensile stress. DF 15 H 95 S 60 refers to a hydrogel prepared by heating and stretching a 15% concentration silk fibroin hydrogel at 95 °C to a 60% tensile magnification. As can be seen from Figure 8, as the concentration of silk fibroin increases, the directional effect of the scaffold becomes more and more obvious, and the tensile properties of the scaffold become better and better. Theoretically, when the concentration of silk fibroin is 20% or more, the tensile properties will be further improved, but due to the limited freeze-drying effect, the tensile properties will be reduced. Therefore, it is determined that 15% is a better silk fibroin concentration.

[0082] Example 5. The effect of different temperatures of heat tension on the performance of silk fibroin hydrogel scaffolds This example uses the method provided by Example 1 to prepare silk fibroin hydrogel. First, DSC detection is performed after step c, and the result is shown in FIG. 9. In the first heating using water molecules as plasticizer, the glass transition temperature of silk fibroin is about 77°C. In the second heating, the water is completely lost from the scaffold and the plasticizing effect of water molecules is lost, so the glass transition temperature of silk fibroin scaffold is increased to 178°C. Therefore, in step d, four temperatures were set by changing the heating temperature during tension (25 ° C, 60 ° C, 95 ° C, 130 ° C), the maximum tensile stress of the prepared hydrogel scaffold was examined, and the mechanism of the scaffold was tested using a biomechanical testing machine, and the tensile curve and mechanical comparison of silk fibroin hydrogel are shown in Figure 10, and it can be seen that before the glass transition temperature (77 ° C), there is no significant difference in the tensile properties of the hydrogel scaffolds prepared at 25 ° C and 60 ° C, and after the temperature is raised to the glass transition temperature (77 ° C), the mechanical properties of the hydrogel scaffold prepared at 95 ° C are significantly higher than those of the other groups, and when the temperature reaches 130 ° C, the scaffold will break when stretched to 60% due to the rapid loss of water molecules, and the mechanical properties will decrease instead. The results show that heating coaxial tension at temperatures above the glass transition temperature can greatly improve the mechanical properties, but this effect will be greatly reduced when the glass transition temperature is raised due to the loss of water molecules. Therefore, it is determined that 95 ° C is a better heating temperature.

[0083] Example 6. Effect of different tension ratios of hot tension on the performance of silk fibroin hydrogel scaffolds This example uses the method provided by Example 1 to prepare silk fibroin hydrogel, and in step d, four tensile ratios are set and stretched using different tensile ratios (0%, 30%, 60%, 90%) to investigate the maximum tensile stress of the prepared hydrogel scaffold, and a biomechanical tester is used to detect the mechanical properties of the scaffold. The tensile curve and mechanical comparison of silk fibroin hydrogel when the tensile ratio increases from 0% to 60% is shown in Figure 11, and the mechanical properties of the scaffold gradually increase, which indicates that as the tensile ratio increases, the directional effect of silk fibroin increases, and when the tensile ratio is further increased to 90%, the excessively high tensile ratio will cause partial breakage of the scaffold, and the mechanical properties of the scaffold will decrease. Therefore, it is determined that the tensile ratio is 60%.

[0084] Example 7: Directional freezing and thermal tension have a synergistic effect on improving the mechanical properties of materials This example relates to three groups of silk fibroin hydrogels, which are obtained by three preparation methods described in Example 1, Example 2, and Example 4, respectively, and they are: ND 15 , D.F. 15 and D.F. 15 H 95 S 60 Figure 12 shows the tensile stress-strain curves of the three groups of hydrogels, as well as the maximum tensile stress and Young's modulus obtained by statistics. ND 15 and DF 15 Comparing the results, it can be concluded that directional freezing alone can increase the maximum stress and Young's modulus of silk fibroin hydrogels by approximately 6-fold and 1-fold, respectively, assuming no heating-tensile step. 15 The hydrogel was further subjected to heat tension, and the DF 15 H 95 S 60 The maximum stress and Young's modulus of the DF are simply 15 The maximum stress increases by approximately 8 and 7 times compared to the hydrogel, and the Young's modulus increases by approximately 58 and 15 times compared to the ND group.

[0085] If neither directional freezing nor non-directional freezing is performed, direct heating and stretching makes the material difficult to stretch and prone to tearing.

[0086] Thus, directional freezing and thermal tensioning have a synergistic effect on enhancing the mechanical properties of non-directional hydrogels.

[0087] Example 8 Repair effect of silk fibroin hydrogel obtained under optimal conditions in rabbit tendon rupture model Defender 15 H 95 S 60 The hydrogel has a tensile strength and Young's modulus similar to those of tendons, and exhibits DF in vivo. 15 H 95 S 60 The hydrogel decomposes very slowly, providing stable mechanical properties over a long period of time, making it a promising candidate for an artificial tendon substitute. DF 15 H 95 S 60 To test the potential of the hydrogel as a tendon patch, rabbit Achilles tendons were transected and a DF was applied to the tendon stump, which acts as a splint providing mechanical compensation and a growth template while retaining tension in the tendon. 15 H 95 S 60 The hydrogel is sutured. As shown in Figure 13, in the early stage of repair (4 weeks), new tendons appeared in all groups (blue arrows), but the new tendons in the fracture group were arranged in a disorderly manner, the cell nuclei were more numerous and rounder, and more vascularized, partially fatty (yellow arrows), and DF 15 H 95 S 60 The new tendon of the group is basically DF 15 H 95 S 60 The nuclei are essentially spindle-shaped, and their morphology is more similar to that of normal tendons. 15 H 95 S 60 It was found that only a thin layer of fibrosis and immune reaction zone was present around the DF. 15 H 95 S 60 It shows good biocompatibility. DF 15 H95 S 60 The tendons themselves show little degradation and retain high integrity (white arrows). Due to the lack of sufficient mechanical conditions, the ND group undergoes fracture / displacement and cannot provide effective mechanical support, and the new tendons are similar to those in the fracture group. At 12 weeks, the new tendons in the ND and fracture groups are arranged in large waves, whereas the DF 15 H 95 S 60 The tendons were cleaner in the DF group. 15 H 95 S 60 The new tendons in the group were very close to normal tendons and had no obvious pathological differences from normal tendons.

[0088] The invention shown and described herein can be practiced without any of the elements or limitations specifically disclosed herein. The terms and expressions used are intended as terms of description and not of limitation, and the use of these terms and expressions is not intended to exclude the features shown and described or portions thereof, and it will be recognized that various modifications are possible within the scope of the invention. It should therefore be understood that although the invention has been specifically disclosed with respect to various embodiments and optional features, those skilled in the art may adopt modifications and variations of the concepts described herein, which are deemed to be within the scope of the invention as defined by the appended claims.

[0089] The contents of all articles, patents, patent applications, and other literature and electronically available information described or recorded herein are incorporated herein by reference in their entireties to the same extent as if each individual publication was specifically and individually indicated to be incorporated by reference. Applicants reserve the right to incorporate into this application any and all materials and information from such articles, patents, patent applications, or other documents.

Claims

1. 1. A method for preparing a hydrogel comprising the steps of: (1) performing directional freezing on a solution containing silk fibroin to change the solvent from a liquid state to a solid state; Step (2) of subliming the solvent in the product obtained in step (1) from a solid state to a gaseous state; and step (3) subjecting the product obtained in step (2) to directional heat drawing to obtain said hydrogel.

2. The preparation method of claim 1, wherein in step (2), the method further comprises cross-linking the silk fibroin.

3. 3. The preparation method of claim 2, wherein in step (2), the method further comprises solvating the cross-linked silk fibroin, and the solvent is the same as the solvent used to dissolve the silk fibroin in step (1).

4. The method of claim 1 , wherein the solvent comprises water.

5. The preparation method according to claim 4, wherein the solvent is pure water or mineral water.

6. The method of claim 4 , wherein the direction of the directional pulling is the same as the direction of the directional freezing.

7. 7. The preparation method of claim 6, wherein step (1) includes providing a freezing source to change a solvent in the silk fibroin solution from a liquid state to a solid state, and bringing the silk fibroin solution close to the freezing source to solidify the silk fibroin solution starting from close to the freezing source toward a direction away from the freezing source.

8. 8. The method of claim 7, wherein in step (1), a silk fibroin solution is injected into a cavity having an opening, and the solution in the cavity is subjected to directional freezing.

9. 9. The method according to claim 8, characterized in that the temperature at which water changes from a liquid state to ice is below 0°C.

10. 10. The process according to claim 9, characterized in that the temperature is below -20°C.

11. 11. The method of claim 10, further comprising the step of providing a metal rod in step (1), one end of the metal rod contacting or approaching the solution in the cavity and the other end contacting liquid nitrogen.

12. The method of claim 11, wherein one side of the metal bar covers the bottom of the cavity.

13. The preparation method according to claim 12, characterized in that the crosslinking is chemical crosslinking or enzymatic crosslinking.

14. The preparation method according to claim 13, characterized in that the sublimation method in step (2) includes freeze-drying, the freeze-drying method including: putting the ice block containing silk fibroin into a freeze dryer to freeze-dry, then immersing in absolute ethanol for cross-linking, and then immersing in water for complete hydration; or directly cross-linking the ice block containing silk fibroin, and then sublimating the solvent from solid state to gas state, and then immersing in water for complete hydration.

15. 15. The preparation method according to claim 14, wherein the directional heating and stretching in step (3) refers to heating to or above the glass transition temperature of silk fibroin and then performing directional stretching.

16. 16. The process according to claim 15, wherein the glass transition temperature is less than 80°C.

17. The preparation method according to claim 16, characterized in that the hydrated hydrogel is first preheated at a temperature of 25-130°C, and then the material is stretched to 30-90% of its initial length.

18. A method, comprising: first performing directional freezing on a solvent in a solution containing silk fibroin to change the solvent from a liquid to a solid state, and then freeze-drying to sublimate the solid-state solvent; obtaining substantially solvent-free silk fibroin; and then performing directional heat tensioning on the dried silk fibroin, wherein the heating temperature is higher than the glass transition temperature of the material, and the material is silk fibroin.

19. The method of claim 18 , wherein the direction of the directional pulling is the same as the direction of the directional freezing.

20. 20. The method of claim 19, wherein the solvent is water.